Comparative evaluation of Nannochloropsis oceanica oil and conventional oils on survival, growth, and immunity in nursery rohu (Labeo rohita): towards sustainable aquaculture feeds - Mohanty, Aradhana; Das, Krushna Chandra; Kumari, Rakhi; Chandan, Nitish K.; Nandi, Samiran; Sahoo, Pramoda Kumar; Arumugam, Muthu (Frontiers in Marine Science, 2025)
IntroductionNannochloropsis oceanica CASA CC201 is a marine microalga valued for its capacity to accumulate high levels of polyunsaturated fatty acids, particularly essential omega-3 fatty acid EPA. In carp nursery culture, low survival rates from spawn to fry (25–30%) and from fry to fingerling (40–50%) are often attributed to inadequate access to easily digestible, high-quality nutrients. This study evaluated the potential of N. oceanica–derived algae oil as a sustainable dietary lipid source to improve growth, survival, immune responses, and gut enzymatic activity in nursery-reared rohu (Labeo rohita).MethodsA three-week feeding trial was conducted using four iso-nitrogenous and iso-lipidic diets formulated with fish oil (FO), N. oceanica algae oil (AO), linseed oil (LO), or sunflower oil (SFO). Each diet was randomly assigned to triplicate groups across 12 indoor nursery tanks (2000 L), with 2000 rohu spawn stocked per tank in a completely randomized design. Fish were fed twice daily, aeration was maintained continuously, and weekly water renewal ensured optimal water quality. Growth performance, survival, non-specific immunity parameters (lysozyme, haemolytic, haemagglutination, and myeloperoxidase activities), and digestive enzyme activities (amylase, protease, and lipase) were assessed at the end of the experiment.ResultsThe AO diet resulted in the highest survival among nursery rohu, while the FO diet produced the greatest growth performance. Gut enzyme analysis indicated the highest amylase activity in fish fed FO and the highest lipase activity in fish fed AO, with protease showing no marked trend among treatments. No significant differences were detected in non-specific immune parameters across dietary groups.DiscussionAlgae oil derived from N. oceanica demonstrated clear advantages in enhancing survival and lipase activity, outperforming conventional plant oils and offering a viable partial or complete replacement for fish oil in nursery diets. Although FO supported superior growth, AO provided a more sustainable alternative that could improve overall nursery performance without compromising immunity. These findings underscore the potential of microalgal oils as functional and eco-friendly lipid sources for early-stage carp aquaculture.